Teaching and Learning at Orientation: How UMBC’s New Student Orientation Supports Academic Success - Kőrössy, László; King, Gina (My University, 2025)
The success of UMBC’s mission of transformative education is possible only within the context of a student body aligned with that mission. Enrollment Management is tasked with the responsibility of creating and perpetuating such a body, and New Student Orientation is the primary tool through which incoming students begin their journeys as new Retrievers. Like UMBC’s instructional classes, Orientation occurs through in-person, remote, and hybrid means.
Ninth Annual Provost’s Teaching and Learning Symposium Program September 19, 2025, Baltimore, MD